Analisis Kebijakan Penerapan Teknologi Artificial Intelligence (Ai) Untuk Meningkatkan Proses Pembelajaran - Rahmah, Suqya; Mustofa, Mustofa; Wasliman, Eva Dianawati; Wasliman, Iim (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the policy of implementing artificial intelligence (AI) technology in improving the learning process in university environments, with a comparative study of the Industrial Engineering Study Program and the Islamic Banking Study Program of Universitas Islam Nusantara. The background of the study is based on the need for higher education to adapt to the development of digital technology, especially AI, in order to improve the quality, efficiency, and accessibility of learning. This study uses a qualitative approach with a compare study method, examining regulations, implementation, and evaluation of AI policies through data collection techniques in the form of interviews, observations, and documentation studies of lecturers and students in both study programs. The results of the study indicate that the application of AI in higher education has great potential in improving learning personalization, administrative efficiency, and educational innovation. However, there are various challenges faced, such as limited infrastructure, lack of human resource readiness, and the absence of clear technical regulations regarding the use of AI, especially regarding ethics, academic integrity, and data protection. This study also found that the success of implementing AI policies is greatly influenced by the support of leaders, the readiness of lecturers and students, and the existence of clear ethical guidelines and regulations.